Hirschsprung's disease associated with a deletion of chromosome 10 (q11.2q21.2): a further link with the neurocristopathies?. Issue 4 (April 1994) - Fewtrell, M S; Tam, P K; Thomson, A H; Fitchett, M; Currie, J; Huson, S M; Mulligan, L M
Abstract : We report a patient with total colonic aganglionosis in association with a deletion of part of the long arm of chromosome 10: (del(10)(q11.2q21.2)). This deletion includes the ret proto-oncogene, which has recently been implicated in multiple endocrine neoplasia type 2A (MEN 2A). The possible links between Hirschsprung's disease and the neurocristopathies and the aetiological role of abnormalities of neural crest development in these conditions are discussed.